Multi-Stakeholder Organising for Sustainability - Sharma, Aarti (Auckland University of Technology, 2007)
Multi-stakeholder dialogue and collaborations have been considered as ‘panacea’ for complex local to global problems confronting governments, businesses and society. And for over a decade now, they have also been increasingly promoted as mechanisms to achieve sustainability. There is, however, a dearth of empirical studies that give deeper insights into the practical dimensions and various implications of such processes for sustainability. This dissertation explores how multi-stakeholder organising processes for sustainability occur in local settings. It relies on a theoretical framework that combines institutional and social movements theoretical perspectives. Such a theoretical cross-fertilisation has been helpful in explaining: (a) how the macro institutional context of sustainable development influences micro interactions of individuals during collaborations; and (b) how those micro interactions may influence the sustainability movement organised at macro societal levels. The dissertation is philosophically based on the principles of critical hermeneutics. It draws on the works of Hans-Georg Gadamer and Jürgen Habermas to understand the nature of reality, society and human relationships. The study also uses literature on sustainable development, organising, dialogue, collaboration, stakeholder engagement, emotions and time. Three cases of multi-stakeholder dialogic collaborations organised to address sustainability of two regions in New Zealand were investigated through observations, interviews with participants and documentary research. These processes were developed in response to a regulatory change in New Zealand – the new Local Government Act (2002) which emphasises sustainable development of communities. The data across the three cases was analysed using principles of grounded theory and critical hermeneutics. Analysis reveals how various kinds of institutional pressures (engulfing cultural-cognitive, regulative and normative institutions connected with sustainable development) confront different stakeholders with varying intensities. Those pressures influence stakeholders to become involved in and commit to such collaborations. And as stakeholders participate in such processes, they are shown to engage with one another rationally and emotionally, and with different conceptions of time. The collaborations thus can be characterised by a complex fusion of rationality, emotionality and temporality. On the one hand, multi-stakeholder dialogic collaborations stimulate learning, facilitate relationship building and build social capital for implementing sustainable development. They thus prove themselves as potent governance mechanisms that can help to institutionalise sustainable development. On the other hand, multi-stakeholder dialogic collaborations for sustainability are highly messy, unpredictable, paradoxical and conflict-ridden processes of stakeholder engagement. They are shown to suffer from three major problematics: problematic of misunderstandings; problematic of stakeholders’ emotions; and problematic of stakeholders’ time. They thus, ironically and paradoxically, are also problematic solutions for sustainability.
Keywords: Stakeholder theory; Sustainability; Collaboration; Dialogue; Institutional change; Critical hermeneutics